7 - Behind the Curtains of State Power: Religious Groups and the Struggle for Ascendancy in Nigerian Public Institutions - A Critical Appraisal: https://doi.org/10.4314/ad.v35i4.70220 - Obianyo, Nkolika E. (Africa Development, 2021)
In secular states, religion is expected to occupy a backseat in public life; but in states like Nigeria, this is not so as religion, after ethnicity, has turned out to become a major determinant of political behaviour. It serves as both a unifying and a divisive factor. It unifies Nigerians who share the same belief across ethnic lines and, at the same time, puts them in contest with others who hold different beliefs. Hence, there are several contestations along religious lines. The proliferation of these divides has also given rise to the proliferation of these contestations. Traditionally, this contest has been between the Moslem and Christian groups; but contrary to popular opinion, within the two major religious groups there are several other contestations. Today, there is the contest between Pentecostal and non- Pentecostal Christians, Roman Catholics and non-Roman Catholic Christians (especially the Anglican sect). These contests focus on the relative strength of each group or sect in the corridors of state power. Against this backdrop, this article examines the origin and dynamics of this trend with respect to the Christian religious group in Nigeria. It argues that religion, like ethnicity, serves as instrument for the acquisition of state power, public positions and resources, and consequently as an instrument of exclusion and inclusion in the quest for ascendancy among contestants for state power and public positions. The article argues that this trend cannot be divorced from the ‘rentier’ and ‘allocative’ character of the post-colonial state of Nigeria in which occupants of state power not only use the state to improve their material well-being but also that of their primordial groups from which they draw support when the competition gets stiff. The ar ticle examines the implications of this trend for development and efficiency of public institutions in Nigeria.